2018
DOI: 10.3390/w10081000
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Private Household Sand Filters in Removing Nutrients and Microbes from Wastewater in Finland

Abstract: Sand filters have been shown to be an economic and effective solution for wastewater treatment in private households, although the removal of phosphorus (P) may be insufficient. However, P removal can be improved by adding a P-adsorbing material, such as biotite, into the sand filters. The physico-chemical characteristics and the microbial quality of the effluents of family-scale sand filters without adsorbing media (SF), sand filters with a biotite layer (B), and sand filters with a modular filter (MB) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
7
1
1
Order By: Relevance
“…Removal efficiency of organic compounds in this study (26.8%) was similar to that obtained by Alsulaili [45] (17%) and Moges et al [46] (20-25%), and also comparable to results obtained by Santos et al [44] in a study carried out using a filter mesh of 0.130 mm diameter (47%). COD removal efficiency was much lower than the removal efficiency obtained by other authors: Martikainen et al [18]-for conventional buried sand filters (92%), and Abdel-Shafy et al [17]-for a down-flow gravel filter (74%). Higher removal efficiency than this study was obtained by Khalaphallah [47] for commercial sand used in the filtration of swimming pools-55%.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Removal efficiency of organic compounds in this study (26.8%) was similar to that obtained by Alsulaili [45] (17%) and Moges et al [46] (20-25%), and also comparable to results obtained by Santos et al [44] in a study carried out using a filter mesh of 0.130 mm diameter (47%). COD removal efficiency was much lower than the removal efficiency obtained by other authors: Martikainen et al [18]-for conventional buried sand filters (92%), and Abdel-Shafy et al [17]-for a down-flow gravel filter (74%). Higher removal efficiency than this study was obtained by Khalaphallah [47] for commercial sand used in the filtration of swimming pools-55%.…”
Section: Discussioncontrasting
confidence: 57%
“…Sand filters have been studied and applied in greywater treatment; they offer a common, low-cost technology with easy operation and maintenance, and efficient removal of total suspended solids (TSS) [17,18]. Several studies have shown that sand filters efficiently remove COD and TSS [11,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clog matter can considerably reduce pore spaces in the granular medium because of its lower density (Knowles et al, 2011). Clogging is often initiated in the top zone of the main filter layer, where abundant biological growth can occur due to contact between the fine media, nutrients, and organic matter in the influent wastewater (Martikainen et al, 2018). Gajewska (2013) reported that bed clogging is influenced by organic matter accumulation.…”
Section: Introductionmentioning
confidence: 99%